Fructose Metabolism and Cardiac Metabolic Stress - Annandale, M.; Daniels, L. J.; Li, X.; Neale, J. P. H.; Chau, A. H. L.; Ambalawanar, H. A.; James, S. L.; Koutsifeli, P.; Delbridge, L. M. D.; Mellor, K. M. (Frontiers in Pharmacology, 2021)
Cardiovascular disease is one of the leading causes of mortality in diabetes. High fructose consumption has been linked with the development of diabetes and cardiovascular disease. Serum and cardiac tissue fructose levels are elevated in diabetic patients, and cardiac production of fructose via the intracellular polyol pathway is upregulated. The question of whether direct myocardial fructose exposure and upregulated fructose metabolism have potential to induce cardiac fructose toxicity in metabolic stress settings arises. Unlike tightly-regulated glucose metabolism, fructose bypasses the rate-limiting glycolytic enzyme, phosphofructokinase, and proceeds through glycolysis in an unregulated manner. In vivo rodent studies have shown that high dietary fructose induces cardiac metabolic stress and functional disturbance. In vitro, studies have demonstrated that cardiomyocytes cultured in high fructose exhibit lipid accumulation, inflammation, hypertrophy and low viability. Intracellular fructose mediates post-translational modification of proteins, and this activity provides an important mechanistic pathway for fructose-related cardiomyocyte signaling and functional effect. Additionally, fructose has been shown to provide a fuel source for the stressed myocardium. Elucidating the mechanisms of fructose toxicity in the heart may have important implications for understanding cardiac pathology in metabolic stress settings.